Comparison of Electrical Engineering Education Graduate Outcomes with Non-Education Graduates - Ramadhiani, Dhevia Octrina; Ashela, Icha; Dzakira, Novia Salwa; Wijayanti, Krisma Puji; Zulfa, Mila Kamalia (Jurnal Inovasi Pembelajaran Karakter, 2025)
This study was carried out by the authors to compare the accomplishments of graduates of electrical engineering education programs with those of non-educational programs. Four phases of the study were carried out: data collecting, data analysis, and conclusions. The study results indicate differences between the non-electrical Engineering Education program at Semarang University and the Electrical Engineering curriculum at Diponegoro University. The curriculum at Semarang State University for Electrical Engineering Education is more concerned with the quality of graduates working in the educational sector, whereas the curriculum at Diponegoro University for non-electrical Engineering Education is more concerned with the quality of graduates working in the industrial world.